The Shape Analysis at One End of the Flux Tube with Dynamical Quarks - Purev, Battogtokh; Chagdaa, Sodbileg; Galsandorj, Enkhtuya (Proceedings of the Mongolian Academy of Sciences, 2020)
In the deconfinement phase transition, we have analyzed the shape of the one end of the flux tube computed by HISQ configurations in full QCD with (2+1) flavors. The ratio of the longitudinal and transverse profile of the parallel chrome-electric field strength revealed that the transverse profile becomes wider than the longitudinal profile when the temperature increases. Also, we found that the comparison, as a function of the distance between two quarks, likely shows melting distances of the flux tube. The melting distances are different for each temperature. They are R = 1.5 fm at T/Tc = 0.97 and R = 1.2 fm at above the critical temperatures T/Tc = 1.00, 1.03, 1.06 and 1.09.